PURE PREMIER ESTIMATION WITH VASICEK MODEL OF INTEREST RATE - RAMDHANI (NIM: 10114049), FADLI
Based on Otoritas Jasa Keuangan (OJK) Number SE-06 / D.05 / 2013, motor vehicle insurance is a loss insurance product that protects the insured from the risk of loss that may arise in connection with the ownership and use of the vehicle. Based on the above explanation, the policyholder is obliged to pay a sum of money called the premium to the insurer. Determination of insurance premium is determined by loading factor and pure premium. Loading factor include tax costs, corporate profits, and others. While the basic price set by the insurance company is the expected value of the total loss called the pure premium for one period of insurance policy. In this final project, total claims data are analyzed to determine the amount of pure premium monthly motor vehicle insurance. The claim total data is modeled with the compound distribution model, before defining the aggregate distribution first will model the number of claims and the severity of claim with the appropriate probability model. In addition to modeling the claim data will also be modeled the interest rate used to calculate the present value of the pure premium, the interest rate model used is the Vasicek model.